2021
DOI: 10.3390/ijerph18179399
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Socioeconomic Position, Adult Educational Attainment and Health Behaviors: The Role of Psychological Capital and Health Literacy

Abstract: Socioeconomic circumstances during childhood and adulthood are known to negatively affect health promoting behaviors. On the other hand, psychological capital (PsyCap) and health literacy are positively associated with these lifestyle behaviors. We, therefore, reasoned that PsyCap and health literacy might “buffer” the negative influences of socioeconomic circumstances on health-promoting behaviors. Method: We measured subjective childhood socioeconomic position (SEP) and adult educational attainment (as a pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…This may be explainable through a similar cumulative stress/resiliency mechanism as pretrauma life stress, wherein those with lower education have fewer options for alternative employment. Education could also be a proxy for other confounders, such as lower health literacy, 34 a learning disability, incarceration, 35 or limited access to higher education. We note however similar findings of Zajacova et al 16 who also found an inverse relationship between pain and education using a populationbased sample of > 74,000 US adults.…”
Section: Discussionmentioning
confidence: 99%
“…This may be explainable through a similar cumulative stress/resiliency mechanism as pretrauma life stress, wherein those with lower education have fewer options for alternative employment. Education could also be a proxy for other confounders, such as lower health literacy, 34 a learning disability, incarceration, 35 or limited access to higher education. We note however similar findings of Zajacova et al 16 who also found an inverse relationship between pain and education using a populationbased sample of > 74,000 US adults.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of PsyCap have shown to have a positive association with wellbeing and health outcomes such as lower body mass index (BMI) and cholesterol levels (26). Also, PsyCap has shown to mediate the link between a low socio-economic position on the one hand, and health outcomes (23) and health behaviors (27) on the other hand, illustrating the possible buffering effect PsyCap has.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Educational attainment (EA) is a widely recognized social determinant of health, influencing health literacy and health‐related behaviors 3,4 . The generally low level of EA was found to be closely associated with a lower economic status, which in turn often coexists with unhealthy lifestyle behaviors such as alcohol abuse, heavy cigarette smoking, unhealthy diet, and being overweight 4 .…”
Section: Introductionmentioning
confidence: 99%
“…2 Educational attainment (EA) is a widely recognized social determinant of health, influencing health literacy and health-related behaviors. 3,4 The generally low level of EA was found to be closely associated with a lower economic status, which in turn often coexists with unhealthy lifestyle behaviors such as alcohol abuse, heavy cigarette smoking, unhealthy diet, and being overweight. 4 Recent research has indicated that the unhealthy lifestyle behaviors mentioned above can accelerate the loss of musculoskeletal mass and function during the natural aging process, ultimately resulting in musculoskeletal pain.…”
Section: Introductionmentioning
confidence: 99%